2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6611050
|View full text |Cite
|
Sign up to set email alerts
|

Graph theoretical connectivity analysis of the human brain while listening to music with emotional attachment: Feasibility study

Abstract: Benefits of listening to music with emotional attachment while recovering from a cerebral ischemic event have been reported. To develop a better understanding of the effects of music listening on the human brain, an algorithm for the graph-theoretical analysis of functional magnetic resonance imaging (fMRI) data was developed. From BOLD data of two paradigms (block-design, first piece: music without emotional attachment, additional visual guidance by a moving cursor in the score sheet; second piece: music with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…While this meta-analysis shows a consistent view, the picture becomes more fragmented when looking at different types of emotions. Very recently, data-driven methods, such as graph theory, 14 eigenvector centrality mapping, 15 network science [16][17][18] and ICA 19 have been only marginally adopted to investigate functional connectivity during listening to music. Clustering analysis 20,21 has instead not been applied to music neuroscience.…”
mentioning
confidence: 99%
“…While this meta-analysis shows a consistent view, the picture becomes more fragmented when looking at different types of emotions. Very recently, data-driven methods, such as graph theory, 14 eigenvector centrality mapping, 15 network science [16][17][18] and ICA 19 have been only marginally adopted to investigate functional connectivity during listening to music. Clustering analysis 20,21 has instead not been applied to music neuroscience.…”
mentioning
confidence: 99%
“…Authors have shown that musical perception requires the integration of different cortical areas [68]. This highly important concept has led researchers to use connectivity analysis [69][70][71][72] and network theory [73] to examine how different brain regions communicate while listening to music. In this line, related to musical experience, a study carried out in musicians shows synchronization of phase alterations in the alpha band between the right frontocentral cortical regions when musical expectation is violated [74].…”
Section: Eeg Fc While Listening To Musicmentioning
confidence: 99%